التضليل الإعلامي ومنظمة ناشيونال جيوغرافيك دراسة وصفية تحليلية - بونقاب, جمال الدين; نوي, محمد (University of Eloued جامعة الوادي, 2020)
"هذه الدراسة المعنونة بـ ""التضليل الإعلامي ومنظمة ناشيونال جيوغرافيك - دراسة وصفية تحليلية"" تعنى بالبحث فيتلك الظاهرة التي تستخدم من طرف كثير من وسائل الإعلام التي تدّعي الحياد والموضوعية، والتي تدفعها في الغالب جهات ضغط ذات طابع سياسي أو أيديولوجي معين تسعى من خلاله إلى تطويع الجماهير لصالح تلك الجهات الحكومية أو النخبوية. وتنطلق الدراسة من إشكالية رئيسة وهي: ما مدى وجود مؤشرات التضليل الإعلامي في محتوى المادة الإعلامية لمنظمة ناشيونال جيوغرافيك (المجلة، الموقع الالكتروني، القناة)؟ وتتعلق أهمية الموضوع بالمنظمة محل الدراسة وذلك لاعتبارات مختلفة من أهمها عدم وضوح النشاط الحقيقي للمنظمة المعروفة في كثير من الأوساط بالطابع العلمي والتثقيفي. كما تهدف هذه الدراسة إلى: - الكشف عن مدى وجود مؤشرات تضليل إعلامي في المادة الإعلامية للمنظمة. - الكشف عن موضوع المادة الإعلامية للمنظمة والتعرف على مصدرها. - تحديد شكل المادة الإعلامية للمنظمةو التعرف على اللغة المستخدمةفيها. - التعرف على نوع الاستمالة الإقناعية في المادة الإعلامية للمنظمة وأسلوب التضليلفيها. ولتحقيق الأهداف المرجوّة، تم استخدام المنهج الوصفي التحليلي القائم على التفسير والنقد؛ وذلك بتوظيف أساليب وتقنيات مختلفة وهي: تحليل المضمون، والملاحظة. وتمثل مجتمع البحث في جميع المنتجات الإعلامية للمنظمة، كما تمثلت عينات البحث الـ (39) في أعداد من المجلة وعدد من الفيديوهات ومواقع المنظمة وصفحاتها الرسمية. وقد خلصت الدراسة إجمالاً إلى وجود مؤشرات للتضليل في مختلف القوالب الإعلامية للمنظمة على مستوى الشكل والمضمون. "This study, entitled ""Media Misinformation and National Geographic - An Descriptive and Analytical Study"", is concerned with researching this phenomenon that is used by many media outlets that claim impartiality and objectivity, and which are often driven by pressure agencies of a particular political or ideological nature through which they seek to adapt The masses are in favor of those governmental or elite bodies. The study is based on a major problem: What is the extent of the presence of media misinformation indicators in the content of the media material for National Geographic media (the magazines, the website, the channel)? The importance of the subject relates to the organization under study due to various considerations, the most important of which is the lack of clarity of the real activity of the organization known in many circles to the scientific and educational nature. This study also aims to: -Detecting the extent of indications of misleading information in the media material of the organization. - Disclosure of the subject of media material to the organization and identification of its source. - Determine the form of the organization's media material and identify the language used in it - Knowing the type of persuasive grooming in the media material of the organization and the method of misleading it. To achieve the desired objectives, a descriptive and analytical approach based on interpretation and criticism was used. By employing different methods and techniques: content analysis and observation. The research community was represented in all the media products of the organization, and the (39) research samples were represented by issues of the magazine and a number of videos, websites of the organization and its official pages. Overall, the study concluded that there are indications of misinformation in the various media templates of the organization at the level of form and content.
مذكرة ماستر تخصص دعوة واعلام
Keywords: التضليل. الإعلام. الرأي العام. الجمهور. ناشيونال جيوغرافيك.; misinformation. media. general opinion. The audience. National Geographic.